Analisis Pelaksanaan Good Corporate Governance Terhadap Kinerja Keuangan Pada PT. Kedawung Setia Industrial, Tbk Di Surabaya - Cristanto, Efrem; Nasution, ute Chairus; Pratiwi, Ni made (Universitas 17 Agustus 1945 Surabaya, 2021)
This research aims to try how the connection between good corporate governance and variables (institutional ownership, managerial ownership, and Independent commissioning board) towards variable financial performance (return on assets). Application of good corporate governance for company is expected to be able to create the harmony of interests and preventing the appearance of confict, so that a good financial performance is able to reach by the company. The company management need to supervised and controlled to ensure company management is in accordance with the rules so that the harmony of interests be created between the company management and the stockholder so that will able to decrease the probability of interest conflict to be appearing. Whereas the company's financial performance assessment is important to be done whether by the management, stockholder or the government. The objective of the company's financial is to motovate the employee in achieving the organisation's goal and in obeying the preordained standards of behavior, in order to get the desirable actions and results. The type of research which was used is the quantitative research with deductive-inductive approach. This research use the seconday data from the annual financial report of PT. Kedawung Setia Industrial, Tbk registered to the indonesian stock exchange in 2018-2020. The sampling that the author uses a method of research the study of documentation by obtaining data and information in a book form, archive, document, numeric writing and pictures in a report as well as information that could support research. The data analysis technique uses descriptive method that used to analyze data by describing or depicturing data that has been collected in accordance without intending to draw conclusions that apply to general or generalization. The research's result shows good corperate governance (institutional ownership, managerial ownership, and Independent commissioning board) does not take effect to financial performance (return on assets).Keywords : Good Corporate governance, Financial performance